2020
DOI: 10.1109/tits.2019.2926042
|View full text |Cite
|
Sign up to set email alerts
|

Is it Safe to Drive? An Overview of Factors, Metrics, and Datasets for Driveability Assessment in Autonomous Driving

Abstract: With recent advances in learning algorithms and hardware development, autonomous cars have shown promise when operating in structured environments under good driving conditions. However, for complex, cluttered and unseen environments with high uncertainty, autonomous driving systems still frequently demonstrate erroneous or unexpected behaviors, that could lead to catastrophic outcomes. Autonomous vehicles should ideally adapt to driving conditions; while this can be achieved through multiple routes, it would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
54
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(64 citation statements)
references
References 124 publications
1
54
0
Order By: Relevance
“…Many institutions and companies have their own, non-accessible data sets, but in recent years, publicly accessible data sets have increasingly been made available by various organizations. An overview of available data sets can be found in [35], [36]. Zhu et al [37] also show an overview of data sets and try to unify them.…”
Section: ) Sources For Scenariosmentioning
confidence: 99%
“…Many institutions and companies have their own, non-accessible data sets, but in recent years, publicly accessible data sets have increasingly been made available by various organizations. An overview of available data sets can be found in [35], [36]. Zhu et al [37] also show an overview of data sets and try to unify them.…”
Section: ) Sources For Scenariosmentioning
confidence: 99%
“…An autoencoder-based approach for automatic identification of unusual events using small dashcam video and the inertial sensor is presented in [228] that can potentially be used to develop a robust autonomous driving system. Various factors and challenges impacting driveability of autonomous vehicles along with an overview of available datasets for training selfdriving is presented in [229] and challenges in designing such datasets are described in [230]. Furthermore, Dreossi et al suggested that while robustifying the ML systems, the effect of adversarial ML should be studied by considering the semantics and context of the whole system [231].…”
Section: E Testing Of ML Models and Autonomousmentioning
confidence: 99%
“…In fact, the training of deep models requires datasets with a huge number of labeled data though collecting such amount of data is not an obvious task. Hence, this requirement has led to the development of several new sophisticated autonomous driving datasets [18]. In this section, we review various existing public monomodal and multimodal environment perception databases by detailing and observing the characteristics of each one.…”
Section: Existing Public Multimodal Environment Perception Databasesmentioning
confidence: 99%